Impact of the COVID-19 Pandemic on the Psychosexual Functions of Healthcare Workers. Issue 2 (3rd December 2021) - Eroglu, Unsal; Balci, Melih; Coser, Seref; Basboga, Serdar; Ozercan, Ali Yasin; Kizilkan, Yalcin; Guzel, Ozer; Aslan, Yilmaz; Tuncel, Altug
ABSTRACT: Background: A novel infection, COVID-19, emerged in China and soon became a global pandemic. Pandemic conditions have resulted in stress in the workplace and led to anxiety among healthcare workers (HCWs), having negative impacts on different aspects of their lives, including their sexual function. Aim: To evaluate the changes in the anxiety status of HCWs during the COVID-19 pandemic and the impact of anxiety on their sexual functions. Methods: This is a longitudinal study based on an online survey conducted from April 2020 to February 2021 in hospitals designated as pandemic healthcare centers. An online survey link was sent to HCWs that provided consent for participation in the study. The anxiety status of the participants was assessed using the State Anxiety Inventory, and sexual function was evaluated using the International Index of Erectile Function–15 for men and Female Sexual Function Index for women. Outcomes: Scores obtained at the beginning of the pandemic were compared with those obtained at 6 months into the pandemic to determine the changes in the anxiety levels and sexual functions of the HCWs. Results: A total of 399 HCWs participated in the survey, and the median age was 32 (20–60) years. Compared to the beginning of the pandemic, there was a significant increase in the State Anxiety Inventory score of the female and male HCWs at the sixth month of the pandemic. Among the women, the mean total Female Sexual Function Index score was 23.55 ± 8.69 at the beginning of the pandemic and 21.42 ± 8.91 at the sixth month, and there was a significant decrease in all parameters except pain. Among the men, the International Index of Erectile Function–15 total score was 62.75 ± 12.51 at the beginning of the pandemic and 55.1 ± 12.87 at the sixth month, indicating a significant decrease in all parameters. Clinical implications: Considering that the pandemic will continue for a long time, more psychological support should be provided, and interventions should be made to protect the mental health of HCWs. Strengths & Limitations: The strength of the study is that it had a fairly high number of participants across several institutions. However, being conducted in one country and the sample not being randomly selected and being based on voluntariness can be considered as limitations. Conclusion: Our results show that the COVID-19 pandemic has led to an increase in the anxiety levels of both female and male HCWs, and this situation has negatively affected their sexual functions.